1988
DOI: 10.1128/aem.54.6.1420-1425.1988
|View full text |Cite
|
Sign up to set email alerts
|

The mannoprotein of Saccharomyces cerevisiae is an effective bioemulsifier

Abstract: The mannoprotein which is a major component of the cell wall of Saccharomyces cerevisiae is an effective bioemulsifier. Mannoprotein emulsifier was extracted in a high yield from whole cells of fresh bakers' yeast by two methods, by autoclaving in neutral citrate buffer and by digestion with Zymolase (Miles Laboratories; Toronto, Ontario, Canada), a 0-1,3-glucanase. Heat-extracted emulsifier was purified by ultrafiltration and contained approximately 44% carbohydrate (mannose) and 17% protein. Treatment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(75 citation statements)
references
References 22 publications
4
67
1
3
Order By: Relevance
“…The type of method used can have a great influence on the characteristics of the obtained mannoprotein fraction (N uñez et al, 2006). Cameron et al (1988) found similar results in the composition of the extracts obtained by both enzymatic treatment (with zymolase enzyme) and heat treatment. Dupin et al (2000a,b) evaluated different extraction methods and found that the most effective treatment for the release of mannoproteins was performed with zymolase enzyme.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The type of method used can have a great influence on the characteristics of the obtained mannoprotein fraction (N uñez et al, 2006). Cameron et al (1988) found similar results in the composition of the extracts obtained by both enzymatic treatment (with zymolase enzyme) and heat treatment. Dupin et al (2000a,b) evaluated different extraction methods and found that the most effective treatment for the release of mannoproteins was performed with zymolase enzyme.…”
Section: Discussionsupporting
confidence: 67%
“…The extraction of mannoproteins was performed according to the method of Peat et al (1961), modified by Cameron et al (1988). Each yeast strain was activated by three successive cultures in YM broth, incubating each culture at 30°C for 48 h. The final culture was obtained by seeding 4 mL of previous culture in 400 mL of YM broth and incubating at 30°C for 48 h with stirring.…”
Section: Mannoprotein Heat Extractionmentioning
confidence: 99%
“…Protein was estimated by the dye-binding assay (Bradford 1976) with bovine serum albumin used as the standard. Emulsification activity was measured according to the method of Cameron et al (1988), with a slight modification. To 1 mL of mannoprotein suspension, 1 mL of vegetable oil was added and vortexed at high speed for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Saccharomyces cerevisiae is normally used for alcohol fermentation. Mannoprotein extracted from S. cerevisiae has been shown to be an effective bioemulsifier (Cameron et al 1988). The presence of hydrophilic mannose polymers covalently attached to the protein backbone provides the mannoprotein with the amphiphilic structure common to surface active agents and effective emulsifiers (Cooper and Goldenberg 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation